Hemorrhagic Stroke in Patients with a History of Ischemic Stroke - Irawan, Wildan Kautsar; Fitriyani, Fitriyani; Putri, Giska Tri (Medula, 2025)
Stroke is an acute neurological disorder characterized by disruption of the blood supply to the brain, either due to obstruction or bleeding. Stroke is currently still a health problem that causes many disabilities and deaths in Indonesia. Stroke can also cause economic problems because of the disability that arises as a result of stroke and the funds that must be allocated to treat stroke in the national health system. One of the complications of stroke that can occur is recurrent stroke. This study aims to systematically establish a diagnosis in a 42 year old female patient so that the patient can be treated appropriately. The method used is a case report with analysis of primary data obtained through autoanamnesis, alloanamnesis, physical examination and supporting examinations. A 42 year old woman came with complaints of decreased consciousness accompanied by headache, nausea, vomiting, and weakness in the left limbs. The patient had experienced a non-hemorrhagic stroke 3 years ago. The patient was diagnosed with hypertension 7 years ago, the hypertension was not controlled and the patient did not take medication. The patient in this case was diagnosed with hemorrhagic stroke with a history of ischemic stroke. Patients are managed with non-medical, medical and rehabilitative management. In non-medical management, bed rest is performed. Medical management was given mannitol 250/125/125 every 8 hours, domperidone 3x10mg, sucralfate 3x2c, amlodipine 5 mg at night, lisinopril 5 mg in the morning, and paracetamol 3x1000 mg. The patient also underwent physiotherapy.